ДОВГОТРИВАЛИЙ ВПЛИВ 10g-ГІПЕРГРАВІТАЦІЇ СТИМУЛЮЄ МІЖКЛІТИННІ КОНТАКТИ ТА ІНГІБУЄ ПРИКРІПЛЕННЯ ДО СУБСТРАТУ, МІГРАЦІЮ та ІНВАЗИВНІСТЬ МCF-7 КЛІТИН РАКУ МОЛОЧНОЇ ЗАЛОЗИ ЛЮДИНИ - Kannan, S.; Shailesh, H.; Mohamed, H.; Souchelnytskyi, N.; Souchelnytskyi, S. (PH Akademperiodyka, 2023)
Background: G-force is a fundamental force controlling human cells. Cancer is one of the 4 major health challenges in the Space missions. Cancer in Space project evaluates the reaction of human cancer cells to the conditions of the space flights, including an exposure to high g-forces. Aim: Explore an impact of 10 g force on the oncogenic properties of human breast adenocarcinoma cells MCF-7. Materials and Methods: Cells were exposed to 10 g force for 10 days, as part of a 6-week simulation of conditions of a space flight. Then the cells were cultured for one week under normal culture conditions, before performing tests. Cell proliferation, cell viability, cell-cell contact inhibition, migration, and invasiveness were measured. Immunoblotting was used to evaluate expression of proteins. Results: Proliferation, cell-cell interaction and formation of 3D structures, migration, and invasiveness of cells exposed to 10 g were compared to parental cells cultured at 1 g condition. 10 g exposed cells showed a higher propensity for cell-cell contact inhibitions and lower for 3-dimensional growth in dense culture. This correlated with the decrease of proliferation in a dense culture as compared to the parental cells. The decrease of migration, adherence to a surface, and invasiveness was observed for cells subjected to the hypergravity, as compared to the parental MCF-7 cells. Enhanced expression of E-cadherin and phosphorylated pY576-FAK were observed in 10 g exposed cells but no impact on the expression of Erk, pErk, FAK and p53 was detected. Conclusion: The prolonged exposure of MCF-7 cells to 10 g force targets cell-cell and cell-substrate interactions.